TRANSFER OF LITERATURE: The Transformation of Myths, Statues, and Banyuwangi Gandrung Festival - Novi Anoegrajekti; Endang Caturwati; Sudartomo Macaryus (Prosiding Seminar Nasional dan Internasional HISKI, 2023)
Mode of transfer is the art of adapting to a new target work. Therefore, it can potentially be done by adding, subtracting, or changing. It is also a process of transition and conversion from one medium to another. Transfer of rides as a form of revitalization of oral traditions. Usually, the works of art that are adapted are popular works, and known in the world, but there are also works that are only known after the work is adapted. In this study, we discussed the folklore “Sri Tanjung” and the performing arts “Gandrung Banyuwangi”. Sri Tanjung legend, the origin of the name Banyuwangi district told the wife's loyalty to her husband. This legend was often brought up in local arts and culture. Gandrung as a traditional art tend to be a source of inspiration for the emergence of various creative industries, such as literary works, sculptures, souvenirs, and gandrung batik motifs. Some of these opportunities had been used by the community, especially the MSMEs in Banyuwangi. This study focused on explaining the implementation of literary revitalization as one of the efforts to protect literature supported by the Law.No. 5/2017 on Cultural Advancement as an effort to increase cultural resilience and Indonesia's contribution in the midst of world civilization through the protection, development, utilization, and development of culture. Through ethnographic method, this study began by collecting library data from various sources. The library source was complemented by field data obtained through observation, participation, and in-depth interviews with traditional arts actors, community leaders, cultural observers, bureaucrats, and the arts community. The transfer study was analyzed using adaptation theory by exploring the development of sustainable creative adaptation. The practice of adaptation was the essence of storytelling itself. It implied that telling the same story from different points of view can create much different interpretations, and an adapted work is a whole new work. Through the transfer process, it has become an absolute necessity if we want to develop myths, form traditions, and focus on economic development based on creativity and innovation.